2010
DOI: 10.2116/analsci.26.1119
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination Mechanism of Carbon during Dioxin Formation Using Cl-K Near-edge X-ray-absorption Fine Structure

Abstract: Many environmental organic chemicals have chloride in their structure. Thus, researching the chlorination mechanism of carbon is of interest. Dioxins are typically concentrated in fly ash collected from the post-combustion zone during the operation of municipal solid waste incinerators. In this study, we report the application of Cl-K near-edge X-rayabsorption fine structure (NEXAFS) in determining the chlorination mechanism of carbon in fly ash. The separation of a chloride-carbon (C-Cl) bond was readily reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 20 publications
1
29
1
Order By: Relevance
“…From our results, the contrasting effects of SO 2 gas were strongly dependent on the oxide/chloride ratio of Cu in the fly ash. In “real” MSWI fly ash, Cu exists as the oxide and chloride. ,, A high S/Cl ratio resulted in no inhibition of PCDD/Fs with coal cofiring in MFA . In this case, we suggest one possible reason is the low fraction of CuCl 2 in the MFA.…”
Section: Results and Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…From our results, the contrasting effects of SO 2 gas were strongly dependent on the oxide/chloride ratio of Cu in the fly ash. In “real” MSWI fly ash, Cu exists as the oxide and chloride. ,, A high S/Cl ratio resulted in no inhibition of PCDD/Fs with coal cofiring in MFA . In this case, we suggest one possible reason is the low fraction of CuCl 2 in the MFA.…”
Section: Results and Discussionmentioning
confidence: 77%
“…In a previous study, we reported catalytic and direct chlorination of a C matrix by CuCl 2 . , The C matrix was chlorinated in the case of MFA–CuO in the presence of SO 2 gas because reactions and progressed. “Real” MSWI fly ash contained trace Cu, and some part of the Cu exists as the oxide. ,, The major fraction of Cl in real MSWI fly ash was bonded with K (i.e., KCl). , Thus, reactions and may occur practically in real incinerators. Increasing PCDD/Fs with injected SO 2 gas into MFAs has been reported previously, , which was likely at least partly caused by this mechanism, related to the interaction between SO 2 gas and the solid-phase CuO + KCl system.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These were consistent with previous reports. 8,10,34,43 As shown in Figure 2A, differences in the shape of the spectra between 2815 and 2830 eV were large enough to distinguish between aromatic-Cl, aliphatic-Cl, and different species of inorganic Cl.…”
Section: ■ Results and Discussionmentioning
confidence: 99%